Основные категории греческой импортной керамики Немировского городища - Вахтина, М.Ю. (Материалы по археологии, истории и этнографии Таврии, 1998)
This article is devoted to the characteristics of Greek pottery collection found during the excavation of Nemirov settlement in the forest-steppe region of the Bug River, which is kept in the State Hermitage. This collection includes about one hundred artifacts; it consists of fragments of amphoras with sharp bottoms from East Greek centres dated back to the second half of the 7th - the first quarter of the 5th centuries B.C. and samples of painted table vessels, the majority of which are attributed to Rhodos-Ionic pottery of oriental style and are dated back to the last quarter of the 7th - the beginning of the 6th centuries B.C.